To multiply the polynomials \( (3x - 1)(2x + 4) \), we can use the distributive property (also known as the FOIL method for binomials):
- Multiply the first terms: \( 3x \cdot 2x = 6x^2 \)
- Multiply the outer terms: \( 3x \cdot 4 = 12x \)
- Multiply the inner terms: \( -1 \cdot 2x = -2x \)
- Multiply the last terms: \( -1 \cdot 4 = -4 \)
Now, we combine all these results:
\[ 6x^2 + 12x - 2x - 4 \]
Combining like terms gives:
\[ 6x^2 + (12x - 2x) - 4 = 6x^2 + 10x - 4 \]
So the completed polynomial is:
\[ 6x^2 + 10x - 4 \]
Filling in the blanks for your question:
_x^2 + _x + _
is:
6 (for the x^2 coefficient), 10 (for the x coefficient), and -4 (the constant term).
Thus, the answer is:
6, 10, -4